Negotiating sexual and gender diversity in rural and peri-urban KwaZulu-Natal, South Africa. Issue 4 (3rd April 2023) - Epprecht, Marc; Mngoma, Nomusa
Abstract: A noticeable tendency in the first generation of scholarship on sexual orientation and gender identity/expression (SOGIE) in Africa has been the focus on urban or modern institutional settings. A dominant theme is to document people's struggles against stigma, fear and violence to better inform interventions to strengthen human rights and sexual health for all. In some cases, unintentionally, the impression conveyed of Africa is of a continent with cultures that are uniformly, hostile to SOGIE rights. The present study arises from a large survey among boys and men in KwaZulu-Natal, South Africa that problematises that impression. The study revealed unexpectedly high levels of same-sex sexual experience among boys and men in a mostly rural, culturally conservative setting. Following from that revelation, we conducted in-depth interviews to gain insight into their lives. Informants did indeed recount many incidents of discrimination and violence and admitted to sometimes severe emotional health problems. Yet they also spoke of finding love, acceptance, allies, resources, humour and hope for the future. In this paper, we tease out key themes from the interviews in relation to trends in the scholarship.